SNACK BOUQUET MAKING TRAINING DURING THE COVID-19 PANDEMIC - Mukhafidoh Mukhafidoh; Arditya Prayogi (Jurnal Pemberdayaan Masyarakat dan Inovasi, 2022)
Covid is a new disease caused by the SARS CoV-2 virus. This virus began to enter Indonesia in early 2020. This virus has an impact in various sectors, including in the economic sector in the form of a decrease in income. Business actors need the right and fast innovation to create new activities to ensure the sustainability of their business or to open up more innovative business opportunities. During a pandemic when everyone can’t get together and huddle, another alternative to celebrate a special moment is to send a bouquet. A bouquet is usually in the form of a flower bouquet, but now a new innovation has emerged by replacing flowers with a snack bouquet that is cheaper and affordable and can provide other benefits, not only for display but also for consumption.